STRUKTUR KOMUNITAS MAKROZOOBENTOS PADA TIGA MUARA SUNGAI SEBAGAI BIOINDIKATOR KUALITAS PERAIRAN DI PESISIR PANTAI AMPENAN DAN PANTAI TANJUNG KARANG KOTA MATARAM LOMBOK - HARTINI, HUSNAYATI; Arthana, I Wayan; Wiryatno, Joko (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 7 No 2 (2012), 2012)
Increasing the human activity may lead to decrease utilization of river waters quality. The purpose of this study were to find out structure of macrozoobenthos community as bioindicator of waters quality in three estuaries of Ampenan district; find out the chemical and physical conditions of waters; determine the relationship of physical chemical of waters and macrozoobenthos diversity indices. The study was conducted by dividing of each estuary into 10 stations. Community structure and physical chemical waters parameters was analyzed descriptively. The relationship of physical and chemical waters quality parameters with macrozoobenthos diversity indices was analyzed by regression. The results showed that 8 species found in the estuary of Berenyok, 11 species in the estuary of Ancar and 12 species in the estuary of Jangkok. Conditions of community structure in three estuaries balanced enough up to unstable. Physical and chemistry waters quality in three estuaries are still below the quality standard except for Hg. In Berenyok and J angkok estuaries Hg values obtained in excess of standard quality. Pollution levels in the three estuaries ranging from moderate to heavily polluted. There is a linear correlation between macrozoobenthos diversity indices and DO parameter in each estuary.
Keywords: Estuary, Macrozoobenthos, Waters quality